Comparison of macro and micronutrients intake in an Indian subpopulation with acne vulgaris versus controls: an observational study - Shaikh, Anam; Shaikh, Sadiya; Udipi, Shobha A.; Tyebkhan, Gulrez H.; Vaidya, Rama A. (International Journal of Research in Dermatology, 2022)
Background: Diet plays an important role in the development and severity of acne, a debilitating and psychologically distressing skin condition attributable to chronic inflammation. The diverse food cultures, influence of globalisation and confounding genetic and environmental factors have prompted studies of specific diet on acne. However, diet being a controllable factor, it would be useful to discern the beneficial and harmful effects of certain foods on acne. The aim of the study was to compare macro and micronutrient intakes in persons with acne vulgaris versus controls in an Indian subpopulation in Mumbai city. Current case-controlled, prospective, observational survey was conducted during September to December 2017 with 210 participants aged 18 to 40 years. Methods: We used semi-quantitative Food frequency questionnaire and 24-hour recall tests to identify the pattern of food consumption between acne and non-acne individuals. Statistical analysis was performed using “t” test and ANOVA. Results: Our analysis revealed that the individuals with acne consume a higher portion of dairy products, refined cereals and relatively smaller portions of whole cereals. Acne group had a significant lower (p<0.05) intake of pulses, omega-3 and 6 fatty acids, α-linolenic acid than the non-acne group. Significant difference indicated a lower consumption of micronutrients including zinc (p=0.012), thiamine (p<0.05), and niacin (p=0.01) among acne individuals. Conclusions: Study findings suggest an increased consumption of inflammation triggering foods and lower consumption of foods with anti-inflammatory and antioxidant property in the acne group of individuals.